Augustan poetry and the irrational - Hardie, Philip R. (Oxford University Press, 2016)
'Augustan Poetry and the Irrational', with contributions by some of the leading experts of the Augustan period as well as a number of younger scholars, examines the manifestations of the irrational in a range of Augustan poets, including Virgil, Horace, Ovid, and the love elegists, and also explores elements of post-classical reception.